2006
DOI: 10.1354/vp.43-5-695
|View full text |Cite
|
Sign up to set email alerts
|

Neurohistologic and Ultrastructural Lesions in Cattle Experimentally Intoxicated with the Plant Prosopis juliflora

Abstract: Abstract. Intoxication by pods of Prosopis juliflora (mesquite beans) causes an impairment of cranial nerve function in cattle and goats. In goats, vacuolation of neurons in the trigeminal motor nuclei has been reported. To study the lesions in cattle caused by consumption of P. juliflora pods and dry ground pods, eight 6-to 12-month-old male cattle were divided into 4 groups: group 1 was fed a ration containing 50% of pods; groups 2 and 3 received a ration containing 50 and 75% of dry ground pods, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 4 publications
6
38
0
16
Order By: Relevance
“…Neurohistologic and ultrastructural lesions in cattle experimentally intoxicated with Prosopis juliflora were characterized by vacuolation and swollen mitochondria, with the mitochondrial cristae displaced peripherally, disoriented and disintegrating in neurons of the motor cranial nerve nucleus (Tabosa et al 2006). Studies in isolated mitochondria of rat brains showed that juliprosopine stimulates stage-4 cellular respiration and alters the mitochondrial membrane potential and ATP production by inhibiting complex I of the respiratory chain (Maioli et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neurohistologic and ultrastructural lesions in cattle experimentally intoxicated with Prosopis juliflora were characterized by vacuolation and swollen mitochondria, with the mitochondrial cristae displaced peripherally, disoriented and disintegrating in neurons of the motor cranial nerve nucleus (Tabosa et al 2006). Studies in isolated mitochondria of rat brains showed that juliprosopine stimulates stage-4 cellular respiration and alters the mitochondrial membrane potential and ATP production by inhibiting complex I of the respiratory chain (Maioli et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Anteriormente, porém, já se havia comprovado que a ingestão das vagens dessa planta era responsável pela ocorrência de uma enfermidade denominada "jaw and tongue trouble" em bovinos nos Estados Unidos (Dollahite 1964, Kingsbury 1964) e "coquera" em caprinos no Peru (Bacca et al 1963/66). A intoxicação ocorre, também, com o denominado farelo de algaroba, que se obtém por moagem das vagens após secagem adequada (Tabosa et al 2006). No Brasil, a doença foi descrita em bovinos no Rio Grande do Norte (Silva et al 2006), Paraíba e Pernambuco (Dantas & Menezes 1994), e em caprinos na Paraíba (Lima et al 2004).…”
Section: Introductionunclassified
“…Os sinais clínicos, mais evidentes durante a ruminação, são característicos de disfunção de nervos cranianos, principalmente devido à degeneração e desaparecimento dos neurônios do núcleo motor do trigêmeo (Tabosa et al 2000a(Tabosa et al , 2006. Observa-se relaxamento da mandíbula, desvio lateral da cabeça durante a mastigação e ruminação, incoordenação dos movimentos mastigatórios, dificuldade de apreensão dos alimentos, salivação profusa, disfagia e atrofia dos masseteres.…”
Section: Introductionunclassified
“…A doença foi reproduzida experimentalmente em bovinos que ingeriram rações que continham 50% e 100% da alimentação após um período de seis meses (Figueiredo et al 1996), enquanto Tabosa et al (2006) obtiveram a intoxicação após ingestão de dietas com 50% e 75% das vagens durante 45-75 dias e em caprinos com 60-90% de vagens na alimentação por um período de aproximadamente 210 dias (Tabosa et al 2000a).…”
Section: Introductionunclassified